Attitudes of Oral Surgeons and Periodontists towards Immediate Dental Implant Placement - Zemyna Bineviciute; Gintaras Juodzbalys (Stilus Optimus, 2024)
Objectives: This cross-sectional study aimed to evaluate the factors that determine the choice of oral surgeons and periodontists to perform immediate dental implant placement. Material and Methods: An anonymous survey was carried out from January 6, 2024 to February 29, 2024. The questionnaire was distributed online to Lithuanian specialists - oral surgeons and periodontists, who perform implantation procedures. A total of 186 professionals were included in this survey. Chi-square test, its degrees of freedom was used for the analysis of variables. Results: The main reason for refusing immediate implant placement is a periapical lesion greater than 5 mm, reported by 91.7% of oral surgeons and 96.9% of periodontists. Good aesthetics and preservation of anatomical structures are identified as an advantage by 99.2% of oral surgeons and 92.3% of periodontists. In the aesthetic zone, for periodontists, the main criterion for choosing a method is the quantitative and qualitative indicators of the soft tissue of the extraction socket 96.9%, and for oral surgeons - the morphology of the bone walls of the socket 87.6%. Only 43.1% of periodontists and 33.9% of oral surgeons are familiar with and use extraction socket morphology assessment classifications for immediate dental implant placement. Conclusions: Taking into account study's results, it is recommended to adjust the teaching programs at Universities and to increase the knowledge of specialists performing dental implantation procedures, by carrying out continuous educational programs.